2022
DOI: 10.3390/polym14153145
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous 3D Chitosan Cryogels for Fastac 10EC Pesticide Adsorption and Antibacterial Applications

Abstract: The pesticide pollution of surface water and wastewater has been recognized as a major worldwide concern due to their persistence in the aquatic environment and the potential adverse effects on human, flora, and fauna health. Apart from pesticides, bio-contamination with various bacterial populations leads to waterborne diseases. Hence, it becomes vital to remove the above-mentioned pollutants from water using a suitable process. Consequently, our study emphasized the potential benefits of a highly porous, che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The study conducted by Maoli Yin et al on chitosan/glycidyl methacrylate‐based cryogels showed that these cryogels have significant antibacterial properties 101 . Porous cryogels based on cross‐linked 3D chitosan (CSGA) can kill 82% of E. coli bacteria, 100% of Listeria monocytogenes bacteria, and 99% of S. aureus bacteria 102 …”
Section: Biomedical Applications Of Polymer Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Maoli Yin et al on chitosan/glycidyl methacrylate‐based cryogels showed that these cryogels have significant antibacterial properties 101 . Porous cryogels based on cross‐linked 3D chitosan (CSGA) can kill 82% of E. coli bacteria, 100% of Listeria monocytogenes bacteria, and 99% of S. aureus bacteria 102 …”
Section: Biomedical Applications Of Polymer Gelsmentioning
confidence: 99%
“…101 Porous cryogels based on cross-linked 3D chitosan (CSGA) can kill 82% of E. coli bacteria, 100% of Listeria monocytogenes bacteria, and 99% of S. aureus bacteria. 102 By adding silver nanoparticles to the cryogel, the resulting cryogel will have antibacterial properties. 103 Cryogels based on gelatin and silver nanoparticles have shown a favorable killing effect on methicillin-resistant S. aureus and P. aeruginosa.…”
Section: Antibacterial Properties Of Polymer Gelsmentioning
confidence: 99%
“…In the frame of wastewater treatment, the adsorption efficiency of prepared materials strongly depends on the number and availability of functional groups containing electron-rich atoms. The native wealth of hydroxyl, amino, carboxyl, and sulfate groups in polysaccharides promotes them as valuable alternatives to synthetic polymers for adsorption of HMIs, dyes, oxyanions, or pesticides from contaminated waters [ 181 , 182 , 186 , 187 ]. Besides their inherent capacity to interact with different pollutants, polysaccharides can also support different chemical modifications, either as a path to generate stable networks (cross-linking), or as a means to graft new multifunctional ligands to augment their sorption performance.…”
Section: Considerations On the Use Of Polysaccharides As Building Blo...mentioning
confidence: 99%
“…For example, CS, the only cationic polysaccharide, can easily react with aldehydes to yield condensates known as Schiff bases. When CS is reacted with dialdehydes (such as GA), cross-linked hydrogel networks are produced [ 29 , 187 ]. Other reactions at the amino groups, including alkylation, thiolation, or phosphorylation, can also be performed to obtain valuable CS derivatives [ 188 , 189 , 190 ].…”
Section: Considerations On the Use Of Polysaccharides As Building Blo...mentioning
confidence: 99%
“…In this context, many water treatment technologies, such as coagulation–flocculation, advanced oxidation, membrane filtration and sorption, have been extensively explored to remove pollutants from water sources [ 4 , 5 , 6 , 7 ]. Of these techniques, sorption is considered to be one of the most promising approaches because of its simplicity and low cost [ 8 , 9 , 10 , 11 , 12 , 13 ]. Since the sorbent plays a key role in the sorption process, developing high-performance sorbents is crucial for the feasibility of applying sorption in water cleanup.…”
Section: Introductionmentioning
confidence: 99%